PENCIPTAAN KARYA SENI LUKIS IMPRESIONISME MIXED MEDIA - Haryono, Santoso (Institut Seni Indoensia Surakarta, 2016)
Research art work titled “Creation of Art Work Impressionism Mixed Media“ aims to create paintings impressionism to approach the creation of mixed media techniques. This study seeks to synergize the strengths and peculiarities of character style impressionism mixed media in a creative, free and unique.Research work is important to do given the current world of art creation is growing, so that it takes the experiments cross-media art. Creation method used is the method of research that began with the development of exploration, experimentation, embodiments, and evaluation. Research work resultswill be useful for the development of the arts, in particular on the development of the creation of works of art.Keywords: Impressionism, art, mixed media.